EVALUASI KEBIJAKAN PENURUNAN STUNTING DI PAPUA: STUDI LITERATUR - Soponyono, Soponyono (Journal of Innovation Research and Knowledge, 2025)
This study aims to evaluate stunting reduction policies in Papua through three main indicators: effectiveness, efficiency, and responsiveness, to see the achievement of the national target of reducing stunting by 14% by 2024. The method used is a qualitative literature study with data analysis from scientific articles, government reports, and international publications from 2018 to 2025. The results show that effectiveness is still constrained by geographical factors, limited health personnel, and low policy adaptation to the local context; efficiency is hampered by high distribution costs, weak inter-sectoral coordination, and minimal use of technology; while responsiveness is influenced by low indigenous community involvement, limited two-way communication, and lack of budget flexibility. The discussion emphasizes the need for strategies based on local wisdom, strengthened cross-sectoral coordination, utilization of health technology, and empowerment of local cadres. It is concluded that policies must be more contextual, adaptive, and inclusive, with performance-based budgets, infrastructure support, and active community participation to accelerate the reduction of stunting in Papua.